Praktik Kebiri (Sterilisasi) Pada Hewan Peliharaan Kucing Untuk Menekan Angka Perkembangbiakan Dalam Perspektif Ma’anil Hadis - Fitria Noviatur Rizki; Nasrulloh (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
At this time, people are competing to have pets, and one of the motivations for owning pets is the current pandemic season. One of the most popular animals to keep is a cat, so it's no wonder the population and types of cats are also increasing. Cats are indeed animals that have lost affection for humans. Humans and cats are very easy to build chemistry with. Many people consider pet cats to be toys that should only be used for entertainment. Often, they don't want the pet cat to breed and channel their lust because it is considered a hassle and cannot give pleasure anymore. Then, in the end, they decided to castrate the cat. There are many differences of opinion in deciding whether to allow or prohibit this decision, but here the author will examine it from the perspective of Ma'anil Hadith. This type of research is descriptive and qualitative in nature and is also supported by empirical research to decide the best solution in making law from the perspective of Ma'anil Hadith. The goal of this research is to arrive at the best legal decision in castrating cats based on Hadith while also considering the benefit aspect. The message for people who decide to castrate a cat is to be careful and consider the benefits that are bigger than the harm.